Ownership of Agricultural Land and Residence For Husband and Wife Who Are Different Citizens (Mixed Marriage) - ., Sriono; ., Risdalina; ., Kusno; Tampubolon, Wahyu Simon; Kumalasari M, Indra (International Journal of Membrane Science and Technology, 2023)
There is a fundamental difference between land and agricultural land. The soil itself is the main component of land and has the bearing capacity so that it can withstand the weight of it and the raw materials for making various kinds of goods. While agricultural land is an area on the surface of the earth that has certain criteria such as atmosphere, soil, geological layers, hydrology, biosphere, and plant and animal populations. Based on the provisions of land law in Indonesia every land can be given rights, such as property rights. This study aims to find out and analyze the ownership rights to agricultural land and residence for married couples with different forms of marriage (mixed). This research was conducted using a normative juridical approach. Legislation, literature, publications, and periodicals on the marriage agreement are the legal sources used. The results of the research show that the provisions of the laws and regulations in Indonesia regarding ownership rights to agricultural land and residence for married couples with different nationalities must be based on the marriage agreement that was made. The form of the marriage agreement that is made contains the separation of assets owned by married couples of different nationalities. Because of Indonesian land law, which states that only Indonesian residents can acquire ownership rights to land.